2016
DOI: 10.1016/j.smim.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreceptors on neutrophils

Abstract: Neutrophils play a critical role in the host defense against infection, and they are able to perform a variety of effector mechanisms for this purpose. However, there are also a number of pathological conditions, including autoimmunity and cancer, in which the activities of neutrophils can be harmful to the host. Thus the activities of neutrophils need to be tightly controlled. As in the case of other immune cells, many of the neutrophil effector functions are regulated by a series of immunoreceptors on the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 217 publications
(304 reference statements)
0
77
0
3
Order By: Relevance
“…Therefore, there is a pertinent need to improve the efficacy of cancer therapeutic antibodies. We and others have previously demonstrated that targeting the interaction between CD47 expressed on cancer cells and the inhibitory immunoreceptor SIRPα expressed on myeloid cells substantially potentiates the capacity of anti-cancer antibodies, including Trastuzumab and Rituximab [11][12][13], for recent reviews see [14][15][16]. Consistent with this notion the clinical response of either breast cancer patients treated with Trastuzumab or Non-Hodgkin lymphoma patients treated with Rituximab was better when CD47 expression levels in the tumor cells were lower [11,13].…”
Section: Introductionmentioning
confidence: 67%
“…Therefore, there is a pertinent need to improve the efficacy of cancer therapeutic antibodies. We and others have previously demonstrated that targeting the interaction between CD47 expressed on cancer cells and the inhibitory immunoreceptor SIRPα expressed on myeloid cells substantially potentiates the capacity of anti-cancer antibodies, including Trastuzumab and Rituximab [11][12][13], for recent reviews see [14][15][16]. Consistent with this notion the clinical response of either breast cancer patients treated with Trastuzumab or Non-Hodgkin lymphoma patients treated with Rituximab was better when CD47 expression levels in the tumor cells were lower [11,13].…”
Section: Introductionmentioning
confidence: 67%
“…Recent research has been focusing on further augmenting the anti-tumor responses of neutrophils, i.e., by trying to switch off the brakes. Neutrophils express a variety of inhibitory receptors on their cell surface ( 211 ) providing potential therapeutic targets for checkpoint-blockade therapy. One well-established example of successful checkpoint-blockade on neutrophils is CD47-signal regulatory protein alpha (SIRPα) disruption ( 212 ).…”
Section: Targeting Neutrophil Activity In Cancer Therapymentioning
confidence: 99%
“…Вопреки примитивным представлениям о противоинфекционном иммунитете с участием нейтрофилов (Нф) данные клеточные элементы иммунной системы способны оказывать регуляторное действие на другие клетки, участвующие в регуляции иммунных процессов (рис. 1) [10]. Неспособность к прямому киллингу внутриклеточных патогенов компенсируется регуляторными свойствами Нф: киллинг происходит опосредованно через Тх 1-го типа [11].…”
Section: роль нейтрофилов в регуляции репродуктивно значимых иммунолоunclassified